Study on Seismic Performance Optimization of Assembly Concrete-Filled Steel Tubular (CFST)-Laced Piers - Chen, Liang; Zuo, Rui; Zhang, Yingao; Yang, Dahai; Li, Jianluan; Wu, Zhigang; Ji, Xuekai (Sustainability, 2023)
This study aims to investigate the seismic behavior of concrete-filled steel tubular (CFST)-laced piers; after verifying the model through engineering tests, the simplified finite element models (S-FEM) and refined ones (R-FEM) with CFST-laced piers are developed in this manuscript, respectively. Through comparison, it is found that the S-FEM can effectively improve analyzing efficiency while meeting the requirements of engineering analysis accuracy. In addition, the seismic response of assembled flange-connected CFST-laced piers bridge was studied based on the S-FEM, and different structural parameters, including pier height, axial compression ratios, steel ratios of CFST columns, steel lacing tube arrangement, and longitudinal slope, are considered to optimize the bridge design scheme. Results indicate that the parameters of 0.1 axial pressure ratios and 1:30 longitudinal slope show superior seismic performance. Meanwhile, the peak axial force and peak bending moment of CFST column limbs occur at the pier bottom, and the flanges, which are subject to larger bending moments, are generally located at the two connection positions above the pier bottom.